Migration of the Eastern Imperial Eagle and Steppe Eagle in Turkmenistan - Eldar A. Rustamov; Khodzhamurad I. Khodzhamuradov; Atamyrat S. Veyisov (Пернатые хищники и их охрана)
A dedicated analysis of spring and fall migration of the Eastern Imperial Eagle (Aquila heliaca) and Steppe Eagle (Aquila nipalensis) in Turkmenistan has never been conducted before. Both species have been considered migratory, although in the last decade some individuals began to overwinter. Wide portions of their flyways pass over Turkmenistan. Both species are more often found and concentrated in the southern half of the country and areas containing an abundance of Great Gerbil (Rhombomys opimus) and Libyan Jird (Meriones erythrourus), especially in population outbreak years.